The Barchester Chronicles [videorecording (DVD)] - Trollope, Anthony, 1815-1882; Giles, David; Pleasence, Donald; Hawthorne, Nigel; Rickman, Alan (Warner Home Video, 2005)
The cozy community of Barchester is rocked from its complacency when a crusade against the Church of England's practice of self-enrichment misfires.